Implikasi Perkawinan Campuran terhadap Status Kewarganegaraan Anak - Hidayat, A. Mufti (Prodi Hukum Tata Negara Fakultas Syariah dan Hukum UIN Sunan Ampel Surabaya, 2013)
This paper discusses about Law No. 12 year 2006, article 6 on the Indonesian citizenship which gives the provisions of dual citizenship status to a child as the implication of the mixed marriage, and analysis of Islamic political jurisprudence perspective toward the provisions of the dual citizenship status. The author concludes that granting the dual citizenship status to a child as the implication of the mixed marriage is nothing but for the sake of enforcing the rights of men, particularly for children. It is so because the childâ€™s rights are part of the Human Rights which must be guaranteed, protected, and fulfilled by parents, families, communities, governments, and states. In addition, It is also as a manifestation of the implementation of UUD 1945, article 26 about the citizensâ€™ rights. Islamic political jurisprudence judges that the dual citizenship status for a child of the mixed marriage for the reason to uphold Human Rights might be justified. Since Islam also upholds Human Rights. But in respect to a childcare, they follow their motherâ€™s citizenship when they have been adult. And when they have already been adult, they haveÂ right to choose their nationality.